PERANCANGAN SISTEM INFORMASI PENDAFTARAN MAHASISWA BARU PADA PERGURUAN TINGGI X BERBASIS WEB - Tintin Chandra (Jurnal TIMES, 2016)
Usage of technology become have become requirement to all kind of activity of society, especially in the world of education. Usage of technology in education in the form of exploiting of information system in the form of online. Information system in designed to use CMS (Context Management System) which implementation into form of E-Business. Usage of CMS in system device at registration of new student a college. New system device try to overcome lacking of a old system which is usage of resource which many. Is for that designed by a minimization system usage of resource and spreading of information able to be more accurate. Device registration of new student candidate use language programing of PHP supported by HTML and of CSS. Usage of new system is not quit of usage of data bases as storage media and data processing, hence for the bases of data used by MySQL. For the process of registration of new student candidate use appliance assist scheme that is UML (Unfield Modelling of Language) covering Use Case Diagram, Activity Diagram. Result of system device expected can assist college in course of processing and is depository of new student candidate, while for the society of and penggunaa of system will be able to assist process registration of new student candidate.